(untitled) (World Bulletin of Public Health, 2022)
Osteoarthritis is both a general medical and socio-economic problem, characterized by the development of functional disorders in the joints, loss of working capacity, disability of patients and, thereby, a decrease in their quality of life, significant financial costs. The review article presented by the authors systematizes modern research by foreign authors, including metabolic shifts, inflammatory processes, immune disorders.